Uma abordagem histórica acerca dos Avanços contábeis decorrentes das reformas implementadas pelo Marquês de Pombal na administração fazendária do Brasil - Colônia de 1777 a 1808 - Vasconcelos, Ana Lúcia Fontes de Souza (2008)
This study aims at highlighting the advances in the accounting science as a result of the policy reforms implemented byMarquis of Pombal in the financial reorganization process of Colonial Brazil from 1777 to 1808. The historical-deductive method was used to analyzemanuscripts which required application of paleography. The results point to the improvements occurred in accounting, especially in control activities both in the fiscal area and in the bookkeeping method, through the introduction of “double-entry accounting” (The VenetianMethod) toBrazil’s governmental accounting. The demand for better qualified professionals created a transformational atmospherewhich led totheformalization of the“A ulas deComércio” (1759), and enabled the development of the first accounting book in Portuguese language (1771) by João Baptista Bonavie.